1997
DOI: 10.1577/1548-8675(1997)017<0525:eosaro>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Angling Regulations on Stunting in Bluegill Populations

Abstract: Stunting in populations of bluegill Lepomis macrochirus is a major management problem in the upper midwestern United States, Traditionally, stunting has been attributed to a lack of food resources. An alternative theory suggests that stunting may result from harvest of the large parental males that inhibit spawning by smaller males, allowing small males to direct energy to reproduction instead of to growth. We used a population model to simulate restrictions on harvest of large males under various conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Jennings et al (1997) suggested that selective exploitation of large bluegill males may decrease the age and size of male maturation. In contrast, however, numerical simulations by Beard et al (1997) showed that low angling mortalities for large bluegill males did not lead to delayed maturation but only to size distributions that were shifted toward larger ®sh.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Jennings et al (1997) suggested that selective exploitation of large bluegill males may decrease the age and size of male maturation. In contrast, however, numerical simulations by Beard et al (1997) showed that low angling mortalities for large bluegill males did not lead to delayed maturation but only to size distributions that were shifted toward larger ®sh.…”
Section: Discussionmentioning
confidence: 86%
“…Yet, the phenomenon of stunted growth and its potential causes have received only little scienti®c attention; in particular, theoretical investigations of the mechanisms that can lead to stunting have been scattered (e.g., Diana, 1987;Post and McQueen, 1994;Nibbelink and Carpenter, 1998). Especially studies on the relation between stunting and life-history adaptations have been lacking (however, see Hayes and Taylor, 1990;Beard et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in long-term declines in many bass populations, attributed to reduced overall recruitment Suski et al 2002). Similarly, the breeding success of other nest-guarding species such as the bluegill Lepomis macrochirus Rafinesque (Beard et al 1997) and the European pikeperch Sander lucioperca (Linnaeus) (Lappalainen et al 2003), are also thought to be detrimentally affected by angling. Based on the findings of this study, complete angling closures are now implemented for August, September and October each year to protect remnant populations of M. ikei in the Mann and Nymboida River system.…”
Section: ; Humphries 2005; Koehn and Harrington 2006)mentioning
confidence: 99%
“…Typically anglers selectively harvest large, male bluegills, which can lead to males maturing at earlier ages and nesting at smaller sizes (Jennings, Claussen & Philipp 1997), resulting in slower growth Ehlinger 1997). Thus, bluegill may be especially vulnerable to growth overfishing, leading to smaller size structures that may persist over time even if harvest of large males ceases (Beard, Drake, Breck & Nate 1997;Beard & Essington 2000). The modelling approaches used in this study to evaluate the potential effectiveness of MLLs did not account for any differences in growth because of density-dependent effects.…”
Section: Discussionmentioning
confidence: 99%